The Use Of Electronic Media To Gratify Cognitive Needs Among The Semelai Heads Of Households In Tasek Bera, Pahang - Abd Latif, Muhammad Pauzi (2005)
Mass media has been used extensively in support of agricultural extension, diffusion of information technology, social reforms, education, and health awareness. Apart from media's advancement and capabilities, the social and environmental circumstances that lead the Semelai heads of households to turn to the mass media in order to gratify their cognitive needs are little understood. Therefore this study was conducted to determine how the Semelai heads of households use radio and lV to acquire and gather information that they need to gratify their cognitive needs which will enable them to present the information in a predictable manner, to define problems, and to seek solutions to them. The respondents for this study are the Semelai heads of households in Tasek Bera, Pahang. The sample size for this study is 266, based on the number of Semelai households in Tasek Bera, Pahang. The findings revealed that radio programmes were believed to possess the characteristics of "keeping their listeners up-to-date on current issues and events and making them understand ways of good life", while N programmes were believed to possess the characteristics of "keeping their viewers up-to-date on current issues and events, and giving them brief accounts of many issues". For the evaluations made. on the media programmes, findings revealed that radio listeners felt that it was "good for radio programmes to have features such as current events, issues and making people understand ways of having a good life", featured in their media programmes. The same features would also be best included in TV programmes. Findings on the gratifications sought and obtained from radio and N programmes revealed that listeners and viewers tuned in and watched development, political and health programmes to gratify their cognitive needs. Correlations and hierarchical regression were done to determine the relationships of beliefs and evaluations with gratifications obtained and whether gratifications obtained influenced the listeners'/viewers' beliefs and evaluations of media programmes. The findings of the study revealed that the gratifications obtained were strongly related to the beliefs of media attributes but were not related to evaluations of those attributes. The belief component correlated more strongly with gratifications obtained than with the evaluation component because gratifications obtained should provide feedback to influence the belief that radio and TV actually possessed certain attributes but should not affect more stable evaluations of those attributes.